Pengaruh Indonesian-Japan Economic Partnership Agreement (IJEPA) terhadap Volume Ekspor Indonesia ke Jepang - Hutasoit, Herman Willy; Sirojuzilam, Sirojuzilam; Irsad , Irsad (Fakultas Ekonomi Universitas Samudra, 2025)
The Indonesian-Japan Economic Partnership Agreement (IJEPA) is an economic partnership agreement between Indonesia and Japan that has been in effect since 2008. However, despite the existence of IJEPA, Indonesia's export volume to Japan has continued to decline. Therefore, this study aims to examine the impact of IJEPA on Indonesia's export volume to Japan. This quantitative research uses the Vector Autoregression model over the period 1999 to 2023. The results indicate that IJEPA has no significant impact on Indonesia's export volume to Japan. Similarly, the Wholesale Price Index and the Rupiah-Yen exchange rate do not have a significant impact on Indonesia's export volume to Japan. The only variable that significantly influences and can predict Indonesia's export volume to Japan in the future is Japan's Gross Domestic Product per Capita.